Introduction to homeland security principles of all-hazards risk management - Bullock, Jane A. (Butterworth-Heinemann is an imprint of Elsevier, 2021)
Written by renowned experts, Introduction to Homeland Security, Sixth Edition, informs users about the concepts and bedrock principles of homeland security. Readers will gain a solid appreciation of the broad range of topics that fall within the expanse of the homeland security umbrella and understand how and why they are so closely interconnected. The text will also provide an overview of the evolutionary process behind modern homeland security structures, which helps users to understand why certain functions exist and how they contribute to national and local security efforts. Unlike most books that focus solely on terrorism, this text covers an expansive range of homeland security topics including all-hazards emergency management, cybersecurity, border and transportation security, immigration and customs enforcement, and others.